(3fSNI eG cJHg GdbQeWi Edi ehdGfG GdMGce HCeQ Gddg CejQ GdeDefjf YfO hUhdg Edi eUQs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje CeG HYO abO hUdfG HGdJQc GdNQGSGfjI hGdNjd GdYQHjI hGdSjha GdgfOjI s
(3BNQgG (B:s
(3hNTi YhGbH GdQOi hNGa Gddg ai GdBNQI hGdChdi hgh MSHfG hcai hEdjg jTjQ cd ef OYi s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJhMjO hGdedd hGdfMds